VARIATION OF DIMENSION AND MOISTURE CONTENT OF Agathis labillardieri Werb. FRUIT BASED ON ITS COLOUR - Encep Rachman (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2007)
Agathis labillardieri fruits can be distinguished according to their colours into three different colours i.e. light green and green. This study examined variation of dimension and moisture content of Agathis labillardieri based on those colours. The fruitys are measured their avarege fruits diameter, fruits length, fruit weight, moisture content and and germination percentage. The expweriment were laid out as a Completely Randomized Design. The result indicated that mature fruits have dark green colour. The charateristics of these green fruits are germination percentage 91 %, moisture content 31.2 %, fruit diameter 8.6 cm, length 8.7 cm and fruit weight 526.97 gr.